Mesoscale geometric modelling of bifurcation in 3D woven T-beam preforms - Brown, Louise P.; Yan, Shibo; Zeng, Xuesen; Long, Andrew C. (2015)
Manipulation of the through-thickness yarn path enables 3D woven reinforcement to separate locally in the form of a bifurcation, creating net-shaped preforms for T- and I-beams. Preforming introduces fibre architecture deformation at the 3D woven bifurcation area. We report a geometric modelling approach to represent the realistic fibre architecture, as a preprocessing tool for finite element analyses. The study started with x-ray micro-computed tomography (µCT) of two 3D woven T-beams varying only by their yarn path at the T-junction area. Supported by the µCT image analysis, a set of mathematical formula were proposed to describe the identified features in the 3D woven T-beams. We then moved on to implement the automated modelling procedure in the open-source software TexGen. Using the weave pattern as input data, TexGen first simulates as-woven flat T-piece. Next, TexGen applies geometric transformation and refinements to simulate the preforming process of T-beams. The paper highlights an efficient approach to model the complex woven bifurcation structure at mesoscale.